THE EFFECT OF LAND USE HISTORY ON NATURAL FOREST REHABILITATION AT CORRIDOR AREA OF GUNUNG HALIMUN SALAK NATIONAL PARK, WEST JAVA INDONESIA - Dian Rosleine; Eizi Suzuki; Atih Sundawiati; Wardi Septiana; Desy Ekawati (Research Center for Biology, 2014)
Corridor area of Gunung Halimun Salak National Park was degraded and fragmented by human activities. However, little is known about recovery process in tropical degraded forest under different land use history. To clarifyvegetation structure and forest recovery related to land use history we placed 22 plots (11 of 10 x 10 m2 in abandoned plantation and 11 of 20 x 20 m2 in secondary forest, respectively). DCA (Detrended correspondence analysis) discriminated the plots into three community groups. Swieteniamacrophylla –Agathisdammaa community in abandoned plantation where had a land use history of clear felling.Maesopsiseminii–Cyathea spp. community had a history of severe human disturbance. Fagaceae-Schimawallichii was in less disturbed forest. Below the plantation canopy, light tolerant species, weeds, grasses, and fern of Dicranopteris linearis were dominant. Some exotic plants spread to the disturbed forest. The less disturbed forest in distant area from village remained in good condition as indicated by dominancy of old forest species. For the forest rehabilitation in severely degraded area, human intervention by planting native species can be suggested to avoid invasive species occupancy as well as accelerate forest recovery.